1984
DOI: 10.2527/jas1984.593823x
|View full text |Cite
|
Sign up to set email alerts
|

Nickel as a “Newer Trace Element” in the Nutrition of Domestic Animals

Abstract: Evidence is reviewed that indicates Ni is an essential element for the chick, rat, pig, sheep and goat. Although a number of possible functions for Ni have been proposed based on in vitro and in vivo studies, the physiological role of Ni in the mammalian or avian system is presently unknown. Rumen bacterial urease has been shown to be a Ni-dependent enzyme and Ni is a component of factor F430 present in methanogenic bacteria. Nickel can interact or influence the metabolism of a number of minerals. Interactions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(27 citation statements)
references
References 47 publications
0
27
0
Order By: Relevance
“…Moreover, Bennis et al (2) explained that higher urea concentrations could be related to restricted food intake, which determines an increase of protein breakdown and thus of urea excretion. When considering the above points (2,5,20,31), the decreased Ni levels in the present study might be speculated to be connected with hypoproteinemia. Hypoproteinemia can cause a negative energy balance such that ruminal degradation of urea can be increased, ultimately increasing the usage of urease, which may cause a decrease in the Ni level.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…Moreover, Bennis et al (2) explained that higher urea concentrations could be related to restricted food intake, which determines an increase of protein breakdown and thus of urea excretion. When considering the above points (2,5,20,31), the decreased Ni levels in the present study might be speculated to be connected with hypoproteinemia. Hypoproteinemia can cause a negative energy balance such that ruminal degradation of urea can be increased, ultimately increasing the usage of urease, which may cause a decrease in the Ni level.…”
Section: Discussionmentioning
confidence: 55%
“…Serum Ni levels in ruminants with fluorosis could not be cited from the literature, but rumen bacterial urease has been shown to be a Ni-dependent enzyme and Ni is a component of factor F 430 , present in methanogenic bacteria (31). Furthermore, researchers reported that serum urea concentrations increased (2,5,20) while total protein levels decreased in animals with fluorosis (2,5).…”
Section: Discussionmentioning
confidence: 99%
“…It occurs in soil, water, and biosphere. Ni is not only an essential element for more than 100 compounds but also an essential element for many animals, microorganisms, and plants [1][2][3]. In animals, Ni deficiency inhibits growth, reduces reproductive rate, alters glucose and lipid metabolism, and is associated with anemia, low hemoglobin values, and alterations of metal ion contents [4].…”
Section: Introductionmentioning
confidence: 99%
“…Both types of data are reviewed here in view of their potential usefulness in understanding the modalities of absorption, distribution, metabolism and excretion of the ingested Ni. The present section does not consider results of investigations, carried out with rather low levels of Ni dietary supplementation (often in the order of µg/kg rather than mg/kg feed) and mainly intended to investigate beneficial rather than adverse effects of Ni in different livestock species (Spears, 1984;Bersényi et al, 2004;Prasad and Gowda, 2005;Schaumlöffel, 2012 .1 % and 95.8 % of the added Ni in the three treated groups, respectively, while only very low levels of Ni were excreted by the animals whose diet was not supplemented. Tissue Ni distribution at the two lower Ni levels did not differ from that in control animals.…”
Section: Livestockmentioning
confidence: 99%